2016
DOI: 10.25120/etropic.12.2.2013.3341
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Cinematic Devices to Portray Mental Illness

Abstract: Creative practices that deal with the representation of mental illness potentially have significant social value and relevance; one of these practices is filmmaking and narrative cinema. A film that has recently increased awareness of mental health issues is Silver Linings Playbook (2012). It deals with a family coping with the return of their son, who is being treated for bipolar disorder. “The film gave a fresh face and voice to this issue,” said Patrick Kennedy, cofounder of the brain-research organization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
1
6
0
1
Order By: Relevance
“…But the results did not support the authors' hypothesis: they found that participants used more adjectives with positive connotations to describe the character Charlie than they had used to describe someone with anxiety and depression. Analysing fiction films and television programs, Middleton (2013) explores the symptoms that best represent mental illness (p. 180). In the study she conducted, she notes that one film that promoted increased awareness of mental health problems was Silver Linings Playbook (2012) -a film that will be analysed in this study-and concludes that there is a significant need on the part of filmmakers to create films that represent mental illness (p. 180).…”
Section: The Filmic Representation Of Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…But the results did not support the authors' hypothesis: they found that participants used more adjectives with positive connotations to describe the character Charlie than they had used to describe someone with anxiety and depression. Analysing fiction films and television programs, Middleton (2013) explores the symptoms that best represent mental illness (p. 180). In the study she conducted, she notes that one film that promoted increased awareness of mental health problems was Silver Linings Playbook (2012) -a film that will be analysed in this study-and concludes that there is a significant need on the part of filmmakers to create films that represent mental illness (p. 180).…”
Section: The Filmic Representation Of Mental Healthmentioning
confidence: 99%
“…Rössler (2016), in this line of thought, advocates that "media coverage of mental illness has been consistently negative and inaccurate" (p. 1251) and that "there is no country, society or culture in which people suffering any mental illness have the same social value as people without mental illness" (p. 1250). Middleton (2013) concluded that media representations have a strong impact and social relevance and that most filmic representations, being negative, strongly contribute to the increased stigmatization of illness (p. 180). However, he notes that representations can be positive if they suggest and show that mental health problems can be easily treated, thus contributing to decrease stigma (p. 180).…”
Section: The Contribution Of Film To Mental Representation About Anxietymentioning
confidence: 99%
“…Fortunately, times are changing from the films being criticized for the negative portrayal of psychiatrics and psychiatric conditions to the current times when an increasing number of them are able to provide realistic depictions of character styles and psychopathologic disorders, as well as personal and family dynamics, being reasonably accurate and therefore suitable for psychiatric teaching purposes. Cinema constitutes not only an important source of entertainment, but also an educational tool and a significant influence on people's attitude towards mental illness 7,8,16 .…”
Section: «The Screen Is a Magic Medium It Has Such Power That It Canmentioning
confidence: 99%
“…Psychiatry practice requires skills such as critical and reflective thinking, clinical ethical reasoning, values-based practice and narrative skills, which can be aided by cinemeducation since it offers trainees a vicarious experience of mental illness and the opportunity for reflective observation, thus a deeper understanding of the subject 8,9,[14][15][16] .…”
Section: «The Screen Is a Magic Medium It Has Such Power That It Canmentioning
confidence: 99%
“…Die Fixation auf ›realistische Reprä-sentationen‹ hat zweifelsohne ihre Berechtigung; letztlich sind es oftmals Missin den Medien finden sich bei Otto Wahl (1995) und der Glasgow Media Group (1996). Neuere Auseinandersetzungen von Klein und Lemish (2008), Middleton (2016) und Stollfuß (2018) knüpfen an jene Ergebnisse an.…”
Section: Mediale Konstruktionen Und Der Anti-stigma-diskursunclassified